The Gronnedal-Ika Carbonatite-Syenite Complex, South Greenland: Carbonatite Formation by Liquid Immiscibility - HALAMA, RALF; VENNEMANN, TORSTEN; SIEBEL, WOLFGANG; MARKL, GREGOR (Journal of Petrology, 2004)
The Grønnedal-Ika complex is dominated by layered nepheline syenites which were intruded by a xenolithic syenite and a central plug of calcite to calcite-siderite carbonatite. Aegirine-augite, alkali feldspar and nepheline are the major mineral phases in the syenites, along with rare calcite. Temperatures of 680-910°C and silica activities of 0·28-0·43 were determined for the crystallization of the syenites on the basis of mineral equilibria. Oxygen fugacities, estimated using titanomagnetite compositions, were between 2 and 5 log units above the fayalite-magnetite-quartz buffer during the magmatic stage. Chondrite-normalized REE patterns of magmatic calcite in both carbonatites and syenites are characterized by REE enrichment (La CN -Yb CN = 10-70). Calcite from the carbonatites has higher Ba (∼5490 ppm) and lower HREE concentrations than calcite from the syenites (54-106 ppm Ba). This is consistent with the behavior of these elements during separation of immiscible silicate-carbonate liquid pairs. ε Nd (T = 1·30 Ga) values of clinopyroxenes from the syenites vary between +1·8 and +2·8, and ε Nd (T) values of whole-rock carbonatites range from +2·4 to +2·8. Calcite from the carbonatites has δ18O values of 7·8 to 8·6‰ and δ13C values of -3·9 to -4·6‰. δ18O values of clinopyroxene separates from the nepheline syenites range between 4·2 and 4·9‰. The average oxygen isotopic composition of the nepheline syenitic melt was calculated based on known rock-water and mineral-water isotope fractionation to be 5·7 ± 0·4‰. Nd and C-O isotope compositions are typical for mantle-derived rocks and do not indicate significant crustal assimilation for either syenite or carbonatite magmas. The difference in δ18O between calculated syenitic melts and carbonatites, and the overlap in ε Nd values between carbonatites and syenites, are consistent with derivation of the carbonatites from the syenites via liquid immiscibility.